Modern diagnostic and treatment methods in paranasal sinus malignant tumors - Yu. V. Ulianova; M. A. Engibaryan; V. L. Volkova; N. A. Chertova; I. V. Aedinova; M. V. Bauzhadze; I. V. Pustovaya (Южно-Российский онкологический журнал)
Malignant tumors of the head and neck are still one of the most challenging problems of treatment in modern oncology. The disease affects mainly the capable people (from 30 to 60 years old). Tumor lesions of the paranasal sinuses lead to disability and have a high mortality rate. Head and neck tumors comprise of 20–30 % of all cancer cases. People with early paranasal sinus cancer have minor complaints, their general condition doesn’t get affected so they don’t seek for medical care in a while. As a result, patients start on treatment at tumor grades III–IV. This article provides the most complete information about the causes, frequency and special features of the course of paranasal sinus cancer, as well as about modern methods of it’s diagnosis and combination treatment. Despite the great advances in the treatment of these malignant tumors the three and five year survival rates remain unsatisfactory, which requires a research for new effective treatments. Currently the main treatment methods for these malignant tumors are combination and complex (involving surgery, radiotherapy and chemotherapy) treatments. The standard treatment approach includes radical surgical removal of the primary tumor and metastatic lymph nodes followed by radiation or chemoradiation therapy. Chemotherapy as monotherapy is administered in non-resectable primary or recurrent tumors, distant metastases or when a patient refuses the radical surgery. Improvement of existing treatment methods and development of new ones are an essential need. Earlier detection of the disease requires primary care physicians to be trained to diagnose tumor lesions of the paranasal sinuses, and highly specialized physicians (dentists, otorhinolaryngologists, maxillofacial surgeons, dermatologists) to express their cancer alertness.